Prodrução de filmes finos de SnO2 pelo método de spray pirólise utilizando um forno à gás natural com combustão de filtração - Silva Filho, Iramilson Maia da (2012)
The tin dioxide (SnO2) as thin film can be produce with high transparency to visible light and good electrical conductivity. The SnO2 thin films have many technological applications in industry, mainly in electronic devices that use preview display, such as devices in research laboratories. One of the most promising applications is its use as a transparent conductive oxide in photovoltaic solar cells. Due to its transparency in the visible spectrum and low resistivity, the films of tin dioxide are used as a constituent component of photovoltaic solar cells. The present work aims to use a heat furnace, which uses combustion in porous media technology for the production of thin films of tin dioxide (SnO2) on glass substrates, using the technique of spray pyrolysis. The furnace used has a chamber where the films of SnO2 are sintered and a pre-chamber, where the precursor solution is applied films on glass substrates. Spray gun was adapted to furnace and coupled to the antechamber for the spraying of the solution of tin on glass substrates. The technique of doping thin films of Fluoride was used in order to reduce the resistance to electrical current. The thin films of SnO2 was characterized by their optical transmittance spectrum and electrical resistance. The structure of films of tin oxide was study by x-ray diffraction and atomic force microscopy.